PENGAWASAN RITEL DI KOTA PEKANBARU - Anwar, Rezky; SD, Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Retail trading develops quickly together along with the economic development in Pekanbaru, this case is caused by the strategic geographic location, as the capital city of Riau province. Pekanbaru city also has resource and capital that can be developed by conducting commercial business in order to improve the community welfare. No wonder this achievement make Pekanbaru becomes the center of trading and commercial in Riau province. The rapid development of these retail trading is demanding businessman or the doer to obey the appropriate regulation. This research is using qualitative method, by using three techniques, interviewing, documenting and observing. The researcher applies the theories from Robin and Coulter, they divided the controlling method into four dimensions, standard determining, measuring, comparing, and do the acting. In Pekanbaru retail is controlled by trade and industry department also police of civil service (SATPOL PP).Â The aim of this research is to know about the control of retail trading by trade and industry department and police of civil center.The control has been not maximal due to many factors, such as human sources is not able to take control, the coordination and communication between trade and industry department and police of civil center is not optimal, also the lack of awareness of the businessman or the doer to obey the regulation. Â Keywords: Control, RetailÂ